Arâ’u Syauqy Dhaif Wa Juhûdihi Fi Tajdîd Ta’lîm al- an-Nahwi li Ghair an-Nâthiqîna bi al-Arabiyyah - Setiadi, Fadlan Masykura; Nur Balqis (Program Studi Pendidikan bahasa Arab IAIN Langsa, 2024)
This research aimed to explore the thought and efforts of Shauqi Dhaif in modernizing the teaching of Arabic grammar for non-Arabic speakers as presented in his book